PENERAPAN METODE MIND MAP DALAM PENGEMBANGAN KREATIVITAS ANAK USIA DINI - Yeni Lestari, Ni Gusti Ayu Made (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2020)
Basically, every young children have a potential to be creative and an ability to express themselves creatively, even in different ways and levels. A cavernous chance for creativity and full support from the environment give a very important role in making creative thinking children. Creativity is very important to be developed earlier because it can help the children for solving problems. There are four things that are concerned in developing early childhood creativity, namely: 1) giving mental stimulation, 2) giving conducive environment, 3) creative stimulation, and 4) parent involvement. One of method that can be used in developing early childhood creativity is the mind map method. Mind map is a form of writing note in picture or, visual form in which full of color to make the children easier in remembering and also it can be fun for them. Mind map method for playing activities can make childrenâ€™s brain, both left and right brain, works actively and synergistically. Developing of two groups of brain activity in harmony will produce doubling the basic abilities synergistically too.Â